Il Supercalcolatore Pre-Exascale Leonardo: contributi al Mondo del Patrimonio Culturale - Guidazzoli, Antonella; Liguori, Maria Chiara (Archeomatica, 2023)
In late 2022, the Bologna Technopole unveiled its latest pre-exascale supercomputer, Leonardo. This new supercomputer facility will support a wide range of scientific research and Cultural Heritage initiatives, offering exciting possibilities for various fields of knowledge, particularly in the areas of Big Data and Artificial Intelligence. Cineca VisitLab is actively engaged in multiple EU projects that are expected to greatly benefit from the cuttingedge capabilities of this advanced technology.